1996
DOI: 10.1259/0007-1285-69-819-221
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of left ventricular volume by short axis cine MRI

Abstract: MRI is an established and accurate method of measuring left and right ventricular volumes by summing chamber areas in multiple contiguous slices. Acquisition time may be up to 45 min. We have estimated volumes with gradient echo imaging to test the accuracy of a more rapid method (total acquisition time 15 min) using a recognized echocardiographic algorithm. The results were compared with the spin echo method. We studied 20 patients (mean age 52 years, 15 male) within 6 months of anterior myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Intraobserver and interobserver analysis focusing on the degree of data reliability presented homogeneous data sets for all analyzed parameters in concordance with previously performed studies (Forbat et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…Intraobserver and interobserver analysis focusing on the degree of data reliability presented homogeneous data sets for all analyzed parameters in concordance with previously performed studies (Forbat et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…Before going into clinical routine with the cardiac tool, the intention was to test its capabilities. Since it is well known that spin-echo imaging enables the best documentation of the real anatomy and morphology, but not of functional parameters, we did not use this technique in order to be comparable to in vivo relations in further studies, in which the present MR standard is gradient-cine acquisition [11]. The applied commercially available gradient-EPI technique shortens the scan time in comparison with conventional gradient techniques [7].…”
Section: Discussionmentioning
confidence: 99%
“…In correspondence to high correlation coefficients (r > 0.99) for both ventricular sides as well as both investigators, the method was demonstrated to be observer independent under in vitro conditions. Three-dimensional volume determination has obvious advantages compared with any two-dimensional approach, because the calculation of ventricular volumes by summing up the volumes of contiguous slices is completely independent of geometric assumptions [10,11]. The non-invasiveness and renunciation of radiation are evident advantages of MR imaging in comparison with scintigraphic methods [12], angiocardiography as the given gold standard [13], computed tomography [14], and 2D echo [15].…”
Section: Discussionmentioning
confidence: 99%
“…184 In addition, learning frameworks were used to segment 2-D tagged cardiac MR images. 185,186 [187][188][189][190][191] and wall motion/thickening analysis. [187][188][189] In addition, gated SPECT has been extensively validated against various two-dimensional imaging techniques, such as echocardiography, 192 but there are only a limited number of studies comparing gated SPECT with other three-dimensional techniques such as cardiac MRI, which is considered the reference standard for assessing LV volumes.…”
Section: Computer Tomography (Ct)mentioning
confidence: 99%
“…185,186 [187][188][189][190][191] and wall motion/thickening analysis. [187][188][189] In addition, gated SPECT has been extensively validated against various two-dimensional imaging techniques, such as echocardiography, 192 but there are only a limited number of studies comparing gated SPECT with other three-dimensional techniques such as cardiac MRI, which is considered the reference standard for assessing LV volumes. [193][194][195][196] Visual interpretations of wall motion by observers on the two modalities have been compared along with LV volumes [193][194][195][196] but quantitative comparison for assessment of regional wall motion/thickening has not been reported previously.…”
Section: Computer Tomography (Ct)mentioning
confidence: 99%